Clomiphene citrate versus letrozole with gonadotropins in intrauterine insemination cycle - Jindal, Nikita; Singh, Shakun; Chaudhary, Rachna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: This study aimed to evaluate and compare the efficacy of clomiphene citrate (CC) and letrozole, both alone and in combination with gonadotropins, for ovulation induction in infertile women. Methods: A total of 200 participants were divided into four groups: CC alone, letrozole alone, CC plus gonadotropins, and letrozole plus gonadotropins. Ovulation was monitored via transvaginal ultrasonography, with human chorionic gonadotropin (HCG) administered to trigger ovulation when follicles reached ≥18 mm. Intrauterine insemination (IUI) was performed 24-36 hours post-HCG administration. Results: The letrozole plus gonadotropins group exhibited the highest ovulation rate (86%), followed by CC plus gonadotropins (84%), letrozole alone (72%), and CC alone (70%). Endometrial thickness was significantly greater in the letrozole group (8.53±1.40 mm) compared to the CC group (7.47±0.89 mm; p=0.000), and the size of the dominant follicle was also larger with letrozole (19.20±4.87 mm) than with CC (17.54±5.44 mm; p=0.02). Conclusions: Letrozole, particularly when combined with gonadotropins, may be more effective than CC in inducing ovulation and enhancing endometrial receptivity, thereby potentially improving pregnancy outcomes in infertile women.